'Shanghai is burning': Extravaganza, transgender representation and transnational cinema. Issue 4 (December 2018) - Bao, Hongwei
This article offers a critical analysis of Matthew Baren's 2018 film Extravaganza, a documentary about drag scenes in Shanghai. By focusing on some drag performers represented in this film, in tandem with an examination of the social and industry contexts of the film, as well as my interviews with the filmmaker and performers, I problematise the gender identity of the performers and the national identity of the film. Drawing on Deleuze and Guattari's notion of 'becoming' and Song Hwee Lim's discussion of 'trans', I propose to think about certain modes of transnational production with the critical concept of 'becoming trans'. 'Becoming trans' offers a productive way of conceptualising new modes of 'minor' transnational cinematic connections in a globalised world without having to resort to identity politics.